Art and landscape Buddhist rock sculptures of late antique Swat/Uḍḍiyāna - Filigenzi, Anna (Denkschriften (Österreichische Akademie der Wissenschaften. Philosophisch-Historische Klasse), 2015)
Buddhist rock sculpture of Swat/Uddiyana (7th-8th cent. CE): Analytical study of its aesthetic values, technical concept, historical background and cultural influence.